The effect of media exposure, type of companies, and environmental performance on carbon emission disclosure of Indonesia companies - I Putu Billy Herdiawan; I Gusti Ayu Agung Pradnya Dewi (Review of Management, Accounting, and Business Studies, 2023)
The Effect of Media Exposure, Type of Companies, and Environmental Performance on Carbon Emission Disclosure (CED) in Indonesian Companies (Empirical Studies on Manufacturing Companies Listed on The Indonesia Stock Exchange for the 2016-2018 Period). This study aimed to obtain empirical evidence regarding the effect of Media Exposure, Type of Companies, and Environmental Performance on the disclosure of carbon emissions in manufacturing companies in Indonesia. Measurement of the extent of carbon disclosure was done using a checklist developed based on the information request sheet provided by the CDP (Carbon Disclosure Project). The populations of this study were all manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. The samples of this research were taken from manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018 using the purposive sampling method. There were 15 companies in 2016, 15 companies in 2017, and 15 companies in 2018 that met the criteria as research samples. The classic assumption test was performed for data analysis, and regression analysis was conducted for hypothesis testing. The results of this study indicate that Media Exposure affects the disclosure of corporate carbon emissions in Indonesia, while the Type of Companies and Environmental Performance had no effect on the disclosure of corporate carbon emissions in Indonesia.